Modern paradigm of radioecology and environmental radiation monitoring system - Maria G., Germenchuk (Journal of the Belarusian State University. Ecology, 2020)
The article presents the modern paradigm of radioecology, which considers people and the environment as equal objects of radiation protection and defines the biosphere as an active force affecting radiation safety. Using the result of environmental radiation monitoring in the Republic of Belarus after the Chernobyl disaster, it was shown that the environmental radiation monitoring system, as a mathematical system, obeys system-wide laws, has its main system goals and properties and is typologically heterogeneous, dynamic, open, hierarchical, multi-level and has feedbacks. The article presents rigorousdefinitions of the effectiveness of the environmental radiation monitoring system in terms of linguistic and set-theoretic approaches. This implies that further research is needed to create a holistic description of the system and a forecast of its behavior in various types of exposure situations, which is relevant in the context of commissioning of the Belarusian NPP.
Keywords: paradigm of radioecology; radiation safety; Belarusian NPP; disaster at the Chernobyl NPP; exposure situations; properties of the radiation monitoring system of the environment; typological heterogeneity of the system